2013
DOI: 10.3390/economies1030019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fiscal Policy and Monetary Policy on the Stock Market in Poland

Abstract: Abstract:The focus of this paper is to examine potential impacts of fiscal and monetary policies on stock market performance in Poland. Applying the GARCH model and based on a sample during 1999.Q2 to 2012.Q4, this paper finds that Poland's stock market index is not affected by the ratio of government deficits or debt to GDP and is negatively influenced by the money market rate. The stock index and the ratio of M3 to GDP show a quadratic relationship with a critical value of 46.03%, suggesting that they have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…From the ARDL result in Tables 11 -13, government total expenditure was found to be positively related to stock market development indices (market capitalization ratio, the value of stock traded ratio, and turnover ratio) in line with a priori expectation of a positive linkage. This supports the works of Perveen and Rahman (2018), Onyema (2017), Ali, Zaman, Ziaei, and Anuar (2014) but disagreed with of Ogbulu, Torbira, and Umezinwa (2015), Hsing (2013) and Anghelache, Jakova, and Oanea (2016) on the negative association between government expenditure and development in the stock market. Conventionally, when the government increases its recurrent spending, there would be more funds in the hands of the citizen.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…From the ARDL result in Tables 11 -13, government total expenditure was found to be positively related to stock market development indices (market capitalization ratio, the value of stock traded ratio, and turnover ratio) in line with a priori expectation of a positive linkage. This supports the works of Perveen and Rahman (2018), Onyema (2017), Ali, Zaman, Ziaei, and Anuar (2014) but disagreed with of Ogbulu, Torbira, and Umezinwa (2015), Hsing (2013) and Anghelache, Jakova, and Oanea (2016) on the negative association between government expenditure and development in the stock market. Conventionally, when the government increases its recurrent spending, there would be more funds in the hands of the citizen.…”
Section: Resultssupporting
confidence: 82%
“…Studies on fiscal policy and stock market performance as well as stock market returns have been undertaken by various researchers in Nigeria (see Prukumpai & Sethapramote, 2019;Nwaogwugwu, 2018;Eyo, 2018;Perveen & Rahman, 2018;Onyema, 2017;Kuncoro, 2017;Anghelache, Jakova & Oanea, 2016;Ogbulu, Torbira & Umezinwa, 2015;Ali, Zaman Ziaei & Anuar, 2014;Mutulis & Olweny, 2018;Gowriah, Seetanah, John & Keshav, 2014;Cheng & Sun, 2013;Hsing, 2013;Bekhet & Othman, 2012;Osamwonyi & Evbayiro-Osagie, 2012). However, about stock market development using the World Bank (2013) indices of measuring development in the stock market (stock market capitalization ratio, the value of stock traded ratio, and turnover ratio) have often been ignored in studies conducted in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gertler and Grinols (1982) documented that stock returns are negatively correlated with inflation. In addition, Hsing (2013) found that stock market is negatively affected by inflation rate. Hence, the research hypothesis for the study is:…”
Section: Inflation = (Cpi -Cpi (T-1) )/Cpi (T-1) … … … … (7)mentioning
confidence: 99%
“…However, there are some differences between the researches. Yu Hsing (2013) revealed that the monetary policy affected stock index but it was not correct for fiscal policy in Poland market. Besides, the author also determined the stock index of the U.S and Germany had considerable effect on stock market performance in Poland.…”
Section: Literature Reviewmentioning
confidence: 99%